(1207) Subject guide to periodicals ; accumulative appendix (1962-1976) دليل موضوعي للدوريات؛ ملحق تراكمي (1962-1976) - سميحة مشرقي (معهد التخطيط القومي, 2026)
ملخص تُعد هذه المذكرة البحثية الصادرة عن معهد التخطيط القومي عام ١٩٧٧ دليلاً ببليوجرافياً تراكمياً شاملاً للدوريات الأجنبية التي اقتناها مركز التوثيق بالمعهد منذ تأسيسه عام ١٩٦١ وحتى عام ١٩٧٦، بهدف توفير مرجع استرشادي للباحثين يسهل الوصول إلى المصادر العلمية العالمية. ويقدم الدليل بيانات دقيقة لكل دورية تشمل اسم الناشر ومكان الصدور ونظام التواتر الزمني للإصدارات، مع تصنيف المقتنيات إلى مجموعات موضوعية متخصصة تغطي مجالات حيوية كالاقتصاد والزراعة والبنوك والإحصاء وبحوث العمليات والحواسب الإلكترونية، مما يعكس شمولية المادة العلمية المتاحة وتنوعها لخدمة أغراض البحث والتخطيط القومي الشامل. كما يعتمد الدليل في تنظيمه على منهجية دقيقة ترتب الدوريات موضوعياً ثم أبجدياً، مع تزويد الباحث بفهرس عام للعناوين يربط بين الموضوعات المختلفة وتغيرات مسميات المجلات عبر الزمن لضمان دقة التوثيق. وتبرز أهمية هذا الملف في كونه مرآة للنشاط الفكري والتوثيقي للمعهد، حيث يوضح طبيعة التعاون العلمي الدولي من خلال الدوريات التي يتم الحصول عليها عبر الاشتراك المباشر أو التبادل والإهداء، مما يجعله أداة أساسية لدراسة تطور الفكر التنموي والمصادر المعرفية التي شكلت الرؤى الاقتصادية والاجتماعية في تلك الحقبة التاريخية من تاريخ مصر الحديث. This research memorandum, issued by the National Planning Institute in 1977, is a comprehensive cumulative bibliographic guide to foreign periodicals acquired by the Institute's Documentation Center from its establishment in 1961 until 1976. Its purpose is to provide researchers with a reference guide that facilitates access to international scientific resources. The guide offers detailed information for each periodical, including the publisher's name, place of publication, and publication frequency. The holdings are categorized into specialized subject groups covering vital fields such as economics, agriculture, banking, statistics, operations research, and computer science, reflecting the breadth and diversity of the available scientific material, which serves the purposes of research and comprehensive national planning . The guide is organized using a precise methodology that arranges periodicals thematically and then alphabetically, providing the researcher with a comprehensive index of titles that links different subjects and changes in journal names over time to ensure accurate documentation. The importance of this resource lies in its reflection of the institute's intellectual and documentary activity, illustrating the nature of international scientific collaboration through periodicals acquired via direct subscription, exchange, and donation. This makes it an essential tool for studying the evolution of developmental thought and the knowledge sources that shaped economic and social perspectives during that historical period in modern Egyptian history .